Pengembangan Media Infografis pada Materi Proses Masuknya Hindu Budha untuk Peserta Didik Kelas X IPS SMAN 9 Pontianak: Penelitian - Mohammad Ikhsan; Ika Rahmatika Chalimi; Edwin Mirzachaerulsyah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to determine the development of infographic media on the historical material of the process of entering Hinduand Buddhis tclass X IPS at SMAN 9 Pontianak.There search method used is the product development method (research and development) using the Borg and Gail research model. The results of this research show that: (1) The use of learning media used by teachers is only limited to power point learning media, posters and wall magazines. The teacher's need for infographic learning media can be used as a learning media for sub-material about the entry of Hinduism and Buddhism in Indonesia for class (2) The feasibility of the infographic learning media developed by theresearcher with validation from material experts, theresearcher got an averagescore of 88.46 in the "Good" category and was declared feasible. The validation results from media experts obtained an average score of 100 in the "Good" category andwere declaredworthy.The results of the small group trial obtained an average score of 67.18 in the "Good" category and were declared feasible. Theresultsof the large group trial obtainedan average score of 73.30in the "Good" category and were declared feasible.